Knowledge Of Ovulatory Cycle And Current Fertility Among Women In Ghana - Juayire, C.A (University of Ghana, 2016)
Most studies on knowledge of ovulatory cycle have predominantly established it to have an influence on the effective use of contraception. However studies on knowledge of ovulatory cycle and fertility remains an unexplored area in literature. Filling this gap may prove vital, especially at a time when efforts towards controlling fertility already in place appear to be ineffective. According to the 2014 GDHS, Ghana has experienced a slight increase in TFR from 4.0 in 2008 to 4.2 in 2014. The main aim of the study was to investigate if there exists a relationship between knowledge of ovulatory cycle and current fertility in Ghana. Using the 2014 GDHS dataset and a study sample of 8201 respondents, the univariate analysis results showed that majority of respondents had inaccurate knowledge of ovulation, did not use any method of contraception, were aged 35+ and resided in the urban areas. The bivariate analyses showed that knowledge of ovulatory cycle and current fertility were not significantly related. It was also made evident, from the bivariate analyses that women living with a partner were more likely than married women to have births in the last five years. The Poisson regression model results maintained that knowledge of ovulatory cycle and current fertility were not statistically significant in both regression models. Contraceptive use, age, marital status, ethnicity, level of education and religion were found to be significantly related to current fertility. Among the various recommendations informed by findings from this study, crucial ones include the need for strategies to improve contraceptive use and increase age at first marriage.
Thesis (MA)
Keywords: Knowledge; Ovulatory Cycle; Current Fertility; Women; Ghana